The Effectiveness Of Using Coconut Oil, Aloe Vera And Sirih Kapur To Prevent Striae Gravidarum In Third Trimester Pregnant Women In The Working Area Of The Cilograng Health Center In 2022 - Awal Permata, Fitri; Khairiah, Rahayu (International Journal of Health and Pharmaceutical (IJHP), 2023)
Background : The prevalence of pregnant women with Striae Gravidarum generally ranges from 50-90%. Striae Gravidarum gives itchiness, heat, and dryness, as well as emotional disturbances, causing serious self-confidence problems (Sharon, Salter M, Alexa B, Kimball M, 2006 in Lubis research, Thaufik Wydiawati Suhartono. 2015) Based on research conducted by Uddin SS and Asimas on 80 samples of pregnant women in Pakistan in 2015, various physiologic skin changes were found during pregnancy, the majority of which were changes in pigmentation (70%), linea nigra (54.3%), and striae gravidarum (51.9%). The etiology of Striae Gravidarum is unknown, predispositions include hormonal, skin elasticity, and mechanical stretching. This is why there is no effective method to protect or treat Striae Gravidarum. Writing purpose : This study aims to determine the Effectiveness of the Use of Coconut Oil, Aloe Vera and Kapur Sirih to Prevent Striae Gravidarum in the Work Area of the Cilograng Health Center in 2022. Research methods : This research was carried out because the number of pregnant women who experienced striae gravidarum was 40 people, of the 3rd trimester pregnant women there were 65 people. This research will be conducted at the Cilograng Health Center, Lebak Regency. The subjects to be studied are mothers at the Cilograng Health Center, Lebak Regency. This research was carried out by Quasi Experiment with the Nonequivalent Control Group Design having two groups. Research result : It shows that from 10 respondents, the results of the analysis were obtained after the Strae Gravidae intervention using coconut oil, aloe vera, and whiting was 10.667 with a standard deviation of 714 and a standard error of 292. And the interval estimation results can be concluded that it is believed to be 95%. Conclusions and recommendations : It can be concluded that the effectiveness of coconut oil, aloe vera and whiting has an effect on striaee gravidarum. It is hoped that this research will provide socialization about the prevention of striae gravidarum in third trimester pregnant women so that the prevention of striae gravidarum can be resolved quickly and does not cause striaee gravidarum to become more severe in the Cilograng Health Center Work Area.